Effect of Triclosan and Silver Nanoparticles on DNA Damage Investigated with DNA-Based Biosensor - Jana Blaškovičová; Ján Labuda (Sensors, 2022)
Triclosan (TCS) is a broad-spectrum antimicrobial agent widely used in personal care, healthcare, and clinical practice. One of the most important aspects of toxicological profiling of compounds is their interaction with DNA. In human cells, TCS causes a significant reduction in DNA methylation. The involvement of TCS in chromosomal aberrations, DNA damage, and strand breaks, as well as DNA damage from TCS degradation products, was reported. AgNPs share similarities with TCS in terms of antimicrobial properties, enter the body after exposure, and are used even together with TCS in oral care products. Therefore, their mutual effect on the DNA is of interest. In this study, the electrochemical behavior of TCS on a glassy carbon electrode (GCE) and the biosensor with salmon sperm dsDNA (DNA/GCE), DNA damage by TCS present in phosphate buffer solution pH 7.4 and an additional effect of the immobilized AgNP layer on such DNA damage have been investigated. Two different sizes of AgNPs (about 15 and 37 nm) were tested. Using square-wave voltammetric signals of nucleobases, the portion of survived DNA was 64% in the presence of 15 nm AgNPs compared to 55% in its absence. The protective effect of AgNPs on DNA against TCS-induced DNA damage was found.